Mitos Tenun Gedogan Indramayu sebagai Sistem Kebudayaan Masyarakat Juntikebon - Dewi Mustika; Retno Dwimarwati; Yanti Heriyawati (PANTUN, 2021)
Tenun (weaving fabric) of Gedogan Indramayu is no longer merely a daily clothing in its development. It has been mythized by the user community as a woven fabric that is intended for noble goals in more noble social strata. The four mythical motifs include Babaran, Kluwungan, Poléng Mentisa, and Udan Mas Prambutan motifs. The myth of the weaving of Gedogan Indramayu is used as a guide not only for religious values, but also for the ethics of the people have become part of the culture. Myths in the form of beliefs are actualized in the traditions of the people and in a sacred ceremony, such as: ritual after giving birth, Ruwatan Anak Sukerta, Kirab Kuwu tradition, and Nurubi-Mayat ritual. These traditional ceremonies and rituals are presented as transcendent events. More specifcally, the spirit which cannot be sensed is presented into the material which is tangible. The myth of Gedogan Indramayu weaving has become part of the Junti Kebon cultural system. The values are applied as the patern of the society daily behavior, individually and in society.Keywords: Myth, Babaran, Kluwungan, Poléng Mentisa, Udan Mas Prambutan.